Stafne's Defect with Buccal Cortical Expansion: A Case Report - Flores Campos, Paulo Sérgio (Hindawi Publishing Corporation, 2010)
A rare case of Stafne's bone cavity, type III-G, is reported in a 49-year-old male patient who had been referred to a private clinic for a routine evaluation. The final diagnosis was based on computed tomography. Scintigraphy played a fundamental role in determining the most likely etiology.